Kecerdasan Emosional, Dukungan Sosial dan Stres Kerja Dokter Residen di Rumah Sakit Umum Pusat H. Adam Malik - Rahma Afwina (Mahesa Research Center, 2019)
The aim of this study is to investigated the relationship between emotional intelligence, social support and occupational stress at H. Adam Malik General Hospital Medan. The approach used to this study is quantitative correlational. The study participants were 132 of resident doctors of three departement: surgical, obgyn, and anesthesia. They were selected, making use of total sampling technique. The participants were administrated three questionnaires: emotional intelligence questionnaire, social support questionnaire, and occupational stress questionnaire. Multiple regression analysis was applied as a statistical test to analyze the data. According to results revealed coefficient Freg = 9,682 ( p < 0,05 ). The findings revealed that there was a significant relationship between emotional intelligence, social support and occupational stress at H. Adam Malik General Hospital Medan. The value of emotional intelligence and occupational stress amounts to -0,184 ( p < 0,05 ), it shows that as a emotional intelligence increase, occupational stress will decrease. Subsequently, The value of social support and occupational stress amounts to -0,268 ( p < 0,05 ), it shows that as a social support increases, occupational stress also will decrease.